Perfil diagnóstico de enfermagem de pacientes acometidos por infarto do miocárdio, à luz do Modelo de Florence Nightingale - Martins, Denyse Luckwu (2004)
The infarcts are, in these days, a great problem of world health, in virtue of the crescent number of cases annually. Understanding the importance of the thematic developed a descnptive study, whose objective was to estabiishing, to the light of Florence Nightingaie Conceptual Model and tending for base the taxonomy li of Nanda, a profile nursing diagnosís of patients attacked by the myocardium infarct intemed in unit of intensive therapy (UTJ). The research was accompished at two located hospitais in the municipal distnct of João Pessoa - PB, considered units of reference for attendance to medical emergencies and cardiac surgical. The population of the study was constituted by patients attacked by the myocardium infarct, independent of sex, in the 40 year-old age group or pius, intemed in the unit of intensive therapy, of those institutions. For the organization of the sample, was determined a temporary cutting, dunng which the data of twenty patient were collected, among the ones which 10 (50%) were of the masculine sex and 10 (50%) of the feminíne sex. The predominant age groups were the ones from 43 to 53years with 8 (40%) patient, being the 57 year-old the medium age. It was verified that, the patients met, on average, in the fourtti day of the intem; 17 (85%) patients presented regular general state. Were firmed for those patient 19 different nursing diagnoses, with a total of 148 djagnosis affimiatives and an approximate average of 7 diagnoses for patient. For component of the Florence Nightingale model, 44 (28,4%) belong to the concept Hydration and Nutrition; 29 (18,7%) belong to the componeni Variation; 29 (18,7%) to the component Taiking about hopes and advices; 17 (11%) to the concepts Noise and Iliumination; 15 (9,6%) to lhe component Biood Circulation; 12 (7,7%) to the concept Cleaning and 2 (1,3%) belong to the concept Ventilation. Among the 19 different nursing diagnoses, 8 (40%) obtained a frequency = 50% and started to constitute the profile of nursing diagnosis of patients attacked by the myocardium infarct intemed in UTI, they are: Risk for infection (90%), Disturbed paftem of sleep (85%), Deficient recreation activities (80%), Reduced heart debit (75%), Constipation (70%), Deficit in lhe setf-care for bath/hygiene (60%), Risk for intolerance to the activity (55%) and Anxiety (50%). We believe that the research reached the estabiished objectives and, can contnbute with the ímprovement of the quality of the nursing attendance rendered to the studied dientele.